A Study of the production system of Swift Foods, Inc. - Cortez, Kahna Lynelle; Gabaon, Jennifer Frances; Padre, Ida Felissa (Diliman, Quezon City College of Engineering, 2002)
The Manggahan Processing Plant is one among the many processing plants worldwide in the Philippines whose nature of business is centered in the processing of broiler chickens for local consumption. Its market includes food service establishments, supermarkets and wet markets within the National Capital Region. Its pervasive quality policy centers on food safety and customer satisfaction through responsiveness and on-time delivery. The dressing and killing operations within the plant are facilitated by its automated conveyorized system to produce the freshly dressed chickens. Customization is obtained by way of determining and meeting the needed specifications of the customers, most especially that of the food service establishments (in terms of weight, size, number of cuts, marination needed, etc.) The company readily issues freshly processed chickens and keeps standard buffer inventory levels for their frozen products. The study group, after documenting the company's production system in terms of its company strategies, process management, workforce management, capacity, location and layout planning, aggregate planning, inventory management and scheduling features, has identified three main problems in the company, namely: (1) the non-compliance to the FIFO policy of its warehouse; (2) the need for a forecasting technique; (3) the need for an effective ordering policy and (4) the need for the plant to relocate its operations due to the diminishing supplier base. After analyzing the problems and evaluating the alternatives to address these problems, the study group has come to the following set of recommendations: (1) Implementing a new racking system (2) Using Forecast Including Trend and Seasonality as the appropriate forecasting technique ; and (3) Using a time fence of the two days prior to delivery of its products to the customer. The study group, as an afterthought, considers as further study the alternative of relocating the processing plant as a response to finding more suppliers for its dressing operations. (contract grower farms.)
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Swift Foods Incorporated; Fod industry; Production engineering